Metode-Metode Pelaksanaan PkM (Pengabdian Kepada Masyarakat) Untuk Perguruan Tinggi - Haryono, Eko; Al Murtaqi , Moch. Ridwan; Nur Lailatul Izzah , Armiya; Septian , Damar; Sariman, Sariman (Al Fattah Ejournal Sma Al Muhammad Cepu, 2024)
Community Service (PKM) is one of the important components in the Tri Dharma of Higher Education in Indonesia. This research discusses the methods that can be used in carrying out Community Service in various universities according to several experts and those that are commonly used. This research method uses library research. The results showed that there are 4 methods in carrying out PkM, namely; Participatory Action Research (PAR) method, Service Learning (SL) method, Community-Based Participatory Research (CBPR) method, and Asset Based Community Development (ABCD) method. These methods have been commonly used by various universities, both public and private. However, the implementation can also be adjusted to the conditions and relevance of each university.